Ovid Revisited : the Poet in Exile. - Claassen, Jo-Marie (Bloomsbury Publishing, 2013)
In time for the bimillennium of Ovid's relegation to Tomis on the Black Sea by the emperor Augustus in 8 AD, Jo-Marie Claassen here revises and integrates into a more popular format two decades of scholarship on Ovid's exile. Some twenty articles and reviews from scholarly journals have been shortened, rearranged and merged into seven chapters, which, together with some new material, offer a wide-ranging overview of the exiled poet and his works. ""Ovid Revisited"" treats the poems from exile as the literary culmination of Ovid's oeuvre, ascribing the poet's resilience in the face of extreme h.